﻿Paraphlomis jinggangshanensis (Lamiaceae), a new species from Jiangxi, China - Wan-Yi Zhao; Zhong Zhang; Qiang Fan; Chun-Quan Chen; Wen-Bo Liao; David E. Boufford (PhytoKeys, 2022)
Paraphlomis jinggangshanensis (Lamiaceae), a new species from Jiangxi Province, China, is described and illustrated. The new species is morphologically similar to P. intermedia, but can be easily distinguished from the latter by its cordate leaf base (vs. cuneate, decurrent), stem and calyx tube with glandular hairs (vs. short pubescent), and glabrous anthers (vs. ciliate anthers). A phylogenetic analysis, based on ITS regions, suggests that P. jinggangshanensis represents a separate branch in Paraphlomis and is closely related to Clade II. It is currently known only from Jinggangshan National Natural Reserve. Because of its limited distribution and small population size, the species was assessed as Near Threatened (NT) according to the IUCN Red List Categories and Criteria.